2018
DOI: 10.1080/15384101.2018.1515553
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA hsa_circ_100395 regulates miR-1228/TCF21 pathway to inhibit lung cancer progression

Abstract: circRNA: circular RNA; miRNA: microRNA; RNA-FISH: RNA fluorescence in situy bridization; qRT-PCR: Reverse transcription and quantitative real-time PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
137
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 34 publications
4
137
0
Order By: Relevance
“…This means that the circ_0001649/miR‐331‐3p and circ_0001649/miR‐338‐5p regulatory axis may contribute to tumorigenesis and progression of NSCLC. Hsa_circ_100395 is downregulated in lung cancer tissues and cells and acts as a sponge of miR‐1228 to regulate transcription factor 21 (TCF21) expression, thus inhibiting the proliferation activity, migration, and invasion of lung cancer cells . Another study found that circ_0006916 bound miR‐522‐3p and then directly targeted the PH domain and leucine‐rich repeat protein phosphatases (PHLPP1) .…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…This means that the circ_0001649/miR‐331‐3p and circ_0001649/miR‐338‐5p regulatory axis may contribute to tumorigenesis and progression of NSCLC. Hsa_circ_100395 is downregulated in lung cancer tissues and cells and acts as a sponge of miR‐1228 to regulate transcription factor 21 (TCF21) expression, thus inhibiting the proliferation activity, migration, and invasion of lung cancer cells . Another study found that circ_0006916 bound miR‐522‐3p and then directly targeted the PH domain and leucine‐rich repeat protein phosphatases (PHLPP1) .…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…4 circRNAs, a group of important endogenous non-coding RNAs, mainly consist of transcripts from exons and exert important roles in the downstream gene regulation. 11,12 miRNAs are another group ofnon-coding RNAs containing approximately 22 nucleotides, with a role of regulating gene expression. Thus, compared to their linear counterparts, circRNAs are extraordinarily stable in vivo due to their resistance to exonuclease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, circRNA has_circ_100395 inhibits lung cancer progression through the miR-1228/TCF21 axis, while ciRS-7 promotes oesophageal squamous cell carcinoma tumour growth and metastasis by inducing miR-7/HOXB13 axis. 11,12 miRNAs are another group ofnon-coding RNAs containing approximately 22 nucleotides, with a role of regulating gene expression. 13 A recent evidence suggests that miRNAs are involved in tumorigenesis and tumour development, functioning as gene silencers at a post-transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, circRNAs could regulate the protein function via cap‐independent mechanism, affect the splicing of parental genes and serve as the microRNAs (miRNAs) sponges to cross‐talk with miRNAs . Emerging evidence has proven that circRNAs played important roles in the development of normal tissues and various diseases, such as cardiovascular diseases, age‐related diseases, autoimmune diseases and tumours . Their functions as potential biomarkers were gradually discovered in cancers and neurodegenerative disorders .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Emerging evidence has proven that cir-cRNAs played important roles in the development of normal tissues and various diseases, such as cardiovascular diseases, age-related diseases, autoimmune diseases and tumours. [24][25][26][27][28][29][30] Their functions as potential biomarkers were gradually discovered in cancers and neurodegenerative disorders. 31,32 However, it remains unclear that the comprehensive expression patterns of circRNAs and the roles of them played in the NELL-1-induced osteogenesis of hASCs.…”
mentioning
confidence: 99%